ANALISIS VARIABEL YANG MEMPENGARUHI LOYALITAS PENUMPANG DI UJUNG-KAMAL - Riska Angga Dewi; Sri Purwanto (Management Department, Faculty of Economics and Business, Universitas Jambi, 2023)
Indonesia is an archipelago where ferry transportation is a means of transportation that is often used by the community, which acts as a bridge between islands separated by waters. Ujung-Kamal Port is a crossing that connects Java Island with Madura Island. Since the construction of the Suramadu Bridge in 2009 and the elimination of the entrance fee, the number of passengers in the crossing has decreased. This study aims to determine the effect of 3 research variables namely comfort, safety and reliability which represent indicators of service quality on passenger loyalty for crossing transportation across Ujung-Kamal. This research uses quantitative descriptive method with the determination of respondents using simple random sampling method and for data analysis using SEM PLS application. The SEM PLS application is used to measure the relationship between variables with measuring indicators and to determine the relationship between the independent variable and the dependent variable. Based on the results of the study, it shows that the variables of comfort, safety and reliability have an influence on passenger loyalty across the Ujung-Kamal crossing.